Quality characterization of hot chilli (Capsicum Chinese Jacq.) genotypes in rainy and summer seasons - Robi R (Department of Olericulture, College of Agriculture, 2003)
The research project “Quality chracterization of hot chilli (Capsicum chinense Jacq.) genotypes in rainy and summer seasons” was carried out in the Department of Olericulture, College of Agriculture, Vellayani during 2001 to 2003. The objectives of the study were assessing the magnitude of genetic variability in C. chinense and for identifying superior genotypes for yield and quality based on season and stage of maturity. Ten selected superior genotypes obtained from the preliminary germplasm evaluation trial were used for the study in the two seasons. Analysis of variance revealed significant difference among the genotypes for all the characters studied in both seasons. In rainy season high PCV and GCV were recorded for fruits per plant followed by oleoresin. High heritability coupled with high genetic advance was observed for fruits per plant, oleoresin content and yield per plant. Correlation studies and path coefficient analysis revealed that fruits per plant is the primary yield component as evidenced from its high positive correlation as well as high direct and indirect effects on yield. Significant variation among two seasons was observed for primary branches per plant, days to first flowering, days to harvest, fruit length and yield per plant. The genotypes were generally late in summer for flowering and harvesting. Genotype CC 13 was the earliest in flowering and CC 30 in harvesting in both the seasons. Fruits per plant and yield per plant was maximum in rainy season. In both the seasons, maximum fruits were produced by CC 3 and maximum yield by CC 30. Genotype CC 3 had maximum capsaicin, CC 28 had maximum oleoresin and CC 7 had maximum carotenoid and ascorbic acid content. Quality characters showed significant difference among genotypes, season, maturity and their interactions. Genotypes had good quality in summer. Capsaicin, oleoresin and carotenoid increased as age of fruit increased and reached the maximum at withering stage, whereas ascorbic acid was increased upto red ripe stage and then declined. Bacterial wilt was serious during summer and leaf curl disease during rainy season.